2021
DOI: 10.1080/17515831.2021.1951539
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role of microstructure and temperature on tribological characteristics of fine-grained ZE41 Mg alloy

Abstract: In the current work, ZE41 Mg alloy was processed by friction stir processing (FSP) to achieve grain refinement. In addition to grain refinement, decreased intermetallic phase (MgZn) was also observed after FSP. Increased micro-hardness was observed for the processed ZE41 Mg alloy compared to the unprocessed base alloy. X-ray diffraction (XRD) studies demonstrated the texture characteristics in FSPed ZE41. Reciprocating wear studies conducted at three different temperatures, i.e. room temperature, 125 °C, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The machine learning (ML) methodology was adapted to predict the coefficient of friction (CoF) and wear rate. The dataset for the study was collected from various literature by considering operating temperature (⁰C), hardness of the workpiece and counterpart (HV), normal load (N), the weight percentage of Mg and REE (%) as input parameters and CoF and wear (mm 3 /Nm) as response variables [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ]. For the purpose of comparison, the experimental wear rate in mg is converted into mm 3 /Nm.…”
Section: Experimentation Detailsmentioning
confidence: 99%
“…The machine learning (ML) methodology was adapted to predict the coefficient of friction (CoF) and wear rate. The dataset for the study was collected from various literature by considering operating temperature (⁰C), hardness of the workpiece and counterpart (HV), normal load (N), the weight percentage of Mg and REE (%) as input parameters and CoF and wear (mm 3 /Nm) as response variables [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ]. For the purpose of comparison, the experimental wear rate in mg is converted into mm 3 /Nm.…”
Section: Experimentation Detailsmentioning
confidence: 99%
“…The rate of oxidation was rapid and tribo-oxide layers were formed under air environment. At high temperature, the substrate thermally softens and loses strength, resulting in reduced bonding strength between the oxide layer and the test surface [27]. Under the sliding action, the material plastically yields and gets removed due to shearing.…”
Section: Effect Of Temperature and Environment On Friction Coefficien...mentioning
confidence: 99%
“…The ZE41 alloy exhibits adequate mechanical properties at room and elevated temperatures due to solution and precipitation hardening [25,26]. The tribological characteristics of friction stir processed ZE41 alloy were investigated at elevated temperatures and found that the test temperature significantly affects the wear performance of the alloy [27]. Earlier reports on AZ91 surface composites revealed that the friction and wear characteristics were influenced by the test environment, and oxygen plays a significant role [28].…”
mentioning
confidence: 99%